2023
DOI: 10.1007/s11145-023-10458-8
|View full text |Cite
|
Sign up to set email alerts
|

The home literacy environment and television exposure as mediators between migration background and preschool children’s linguistic abilities

María Valcárcel Jiménez,
Astrid Wirth,
Efsun Birtwistle
et al.

Abstract: The development of key linguistic abilities is essential for young children and their academic success at school, in particular for children with a migration background who are at a greater risk of developing language deficits. Here, family interactions can provide valuable opportunities to support children’s linguistic learning within the Home Literacy Environment (HLE). Although the importance of the HLE for children’s language acquisition has often been investigated, research has not focused on specific fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
0
0
Order By: Relevance
“…Finally, both the digital and analogue HLE were positively associated with academic skills, although the analogue HLE showed higher effect sizes. Another study on children with migration background by [12] found that the association between migration background and children's early linguistic abilities was mediated positively by the HLE and negatively by television exposure.…”
Section: The Impact Of Screen Exposure On Children's Cognitive and Be...mentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, both the digital and analogue HLE were positively associated with academic skills, although the analogue HLE showed higher effect sizes. Another study on children with migration background by [12] found that the association between migration background and children's early linguistic abilities was mediated positively by the HLE and negatively by television exposure.…”
Section: The Impact Of Screen Exposure On Children's Cognitive and Be...mentioning
confidence: 98%
“…However, there is also evidence of positive effects for specific contents (e.g., digital book reading [8], prosocial games [9]), suggesting that some tools might motivate children in learning opportunities [10]. Therefore, digital device use has started to enter into HLE models [11,12].…”
Section: Introductionmentioning
confidence: 99%